2015
DOI: 10.1016/j.colsurfb.2015.05.050
|View full text |Cite
|
Sign up to set email alerts
|

Influence of biocompatible metal ions (Ag, Fe, Y) on the surface chemistry, corrosion behavior and cytocompatibility of Mg–1Ca alloy treated with MEVVA

Abstract: ResumenUno de los materiales más usados como biomaterial es el acero 316LVM; sin embargo, presenta complicaciones al trabajarlo como reemplazo permanente, debido a que libera iones metálicos a los tejidos, generando aumento en el número de intervenciones que deben realizarse; ante esto, se estudia cómo mejorar el comportamiento de materiales convencionales mediante recubrimientos que elevan sus propiedades mecánicas y anticorrosivas, incrementando su vida útil. Se evaluó el comportamiento ante el fenómeno de m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 54 publications
2
37
0
1
Order By: Relevance
“…Both electrochemical and immersion tests revealed the accelerated corrosion rate of Ag-implanted Mg–1Ca and Fe-implanted Mg–1Ca, whereas Y-ion implantation showed a short period of protection as enhanced corrosion resistance was obtained by electrochemical test, but accelerated corrosion rate was found by long-period immersion test. Indirect cytotoxicity assay indicated good cytocompatibility of Y-implanted Mg–1Ca [ 54 ].…”
Section: Mg In Orthopedic Practicementioning
confidence: 99%
“…Both electrochemical and immersion tests revealed the accelerated corrosion rate of Ag-implanted Mg–1Ca and Fe-implanted Mg–1Ca, whereas Y-ion implantation showed a short period of protection as enhanced corrosion resistance was obtained by electrochemical test, but accelerated corrosion rate was found by long-period immersion test. Indirect cytotoxicity assay indicated good cytocompatibility of Y-implanted Mg–1Ca [ 54 ].…”
Section: Mg In Orthopedic Practicementioning
confidence: 99%
“…It was suggested that dual ion implantation of the metallic ion and the oxygen promote corrosion resistance. In addition, the post-oxidation treatment combined with ion implantation can be another solution [ 190 , 268 ].…”
Section: A Methodology For Improving Corrosion Resistancementioning
confidence: 99%
“…The compactness of the composite oxide layer formed at the ion-implanted surface plays a crucial role to enhance the in vitro corrosion resistance. Liu et al [ 186 ] conducted Ag, Fe, and Y ion implantation on Mg -1Ca alloy. The non-uniform aggregation of second phase particles at grain boundaries resulted in an oxide layer with uneven thickness.…”
Section: Coatings and Their Current Statusmentioning
confidence: 99%
“… Substrate Ion implanted ionic oxide layer (nm) Ionic Penetration (nm) In Vitro corrosion conditions I corr uncoated (A/cm 2 ) I corr Coated (A/cm 2 ) Corrosion rate (mm/year) Ref. AZ31 Al 13 SBF , 37.5 °C 2.82 × 10 −5 3.36 × 10 −5 [ 184 ] AZ91 1.50 × 10 −4 5.82 × 10 −5 ZK60 Zr, O 23 80 SBF , 37 °C 4.09 × 10 −4 1.1 × 10 −7 [ 187 ] WE43 Ti, O 32 64 SBF 3.27 × 10 −4 1.44 × 10 −5 [ 191 ] Mg–1Ca Ag 50 70 Hank's solution, 37 °C [ 186 ] Fe 70 110–120 ...…”
Section: Coatings and Their Current Statusmentioning
confidence: 99%